Structural development and stress evolution of an arcuate fold-and-thrust system, southwestern Greater Caucasus, Republic of Georgia. (1st May 2018) - Tibaldi, A.; Bonali, F.L.; Russo, E.; Pasquarè Mariotto, F.A.
Graphical abstract: Highlights: We studied the Rioni arcuate fold-and-thrust belt at the foothill of Greater Caucasus. We recognized four main phases of faulting with different stress fields, plus folding. The belt has along-strike variations in tectonic regime and deformation geometries. We propose it resulted from oblique asymmetric indentation of a crustal block. Field data and seismicity show that this salient has still ongoing tectonic processes. Abstract: The southern front of the Greater Caucasus is quite rectilinear in plan view, with the exception of part of the Rioni Basin, where marine and continental deposits of Cretaceous-Neogene age were locally folded and uplifted; this resulted in the formation of an arcuate fold-and-thrust system that extends 45 km into the foreland. Although previous studies suggested that this system has developed only since Miocene times, our new detailed and systematic field measurements of brittle and ductile structures show a very complex history, consisting in four main phases of brittle deformation and folding, dated from Eocene to Quaternary times. We collected microtectonic data at 248 faults, and calculated the related paleostress tensors. The first two phases which we document here, predated folding and were characterised by dominant transcurrent faulting and subordinate reverse motions; the greatest principal stress σ1 was perpendicular and later parallel to the mountain belt. Afterwards, NW-SE, E-W and NE-SW trending, south-vergent asymmetrical folds started to form. In the western sector of the study area, folds are sinuous in plan view, whereas to the east they show a left-stepping, en-échelon geometry. Another two, brittle deformation phases took place after the folding, due to the activity of a set of right-lateral, strike-slip faults that strike NW-SE and NE-SW, respectively, as well as by left-lateral strike-slip faults, mostly striking NW-SE, NE-SW and NNE-SSW. These two additional phases were produced by a NE-SW to N-S trending σ1 . The arcuate belt is marked by along-strike variations in the tectonic regime and deformation geometry, plus belt-parallel stretching. Based on our field data, integrated with published analogue models, we suggest a possible explanation for the Rioni structure, in terms of the oblique, asymmetric indentation of an upper crustal blocks moving to the SSW.